Effects of physical properties on the compression wave speed of seafloor sediment in the South China Sea: Comparisons between theoretical models and measured data - Tian, Yuhang; Chen, Zhong; Mo, Yaxiao; Xie, Anyuan; Huang, Weixia; Wang, Shuhong; Yan, Wen (Frontiers in Physics, 2023)
The compression wave speed and physical properties of seafloor sediments are significant in ocean engineering explorations, marine geophysics, and underwater acoustics. Although most regression equations can be satisfactorily fitted to the data and provide a useful predictive method, there is little insight into the influence of physical properties on the compression wave speed of seafloor sediment in the South China Sea (SCS). To characterize the compression wave speed and physical properties of seafloor sediments, the compression wave speed, porosity, density, and mean grain size were measured and calculated for forty-two samples collected from the SCS. The results show that the RMS roughness of seafloor sediment in the SCS ranges from 0.2 to 15 μm, and the porosity and density are determined by the RMS roughness and mean grain size. The relationships between the compression wave speed and physical properties of seafloor sediments are consistent with the intergranular friction model. When we have the physical parameters but no compression wave speed, therefore, the intergranular friction model can be used to predict the compression wave speed of seafloor sediment. Compared with the Wood model curve, we also reveal that the intergranular friction of seafloor sediment is an important parameter in determining the compression wave speed.